Edukasi dan Sosialisasi Bahaya Cemaran Bakteri Coliform pada Saus Makanan Jajanan Kepada Masyarakat Desa Amplas Kecamatan Percut Sei Tuan - Yayuk Putri Rahayu; Sri Wahyuni; Ridwanto Ridwanto; Haris Munandar Nasution (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Sauces are often used in street food. Based on previous research results, many street food sauces were found to be contaminated with Coliform. Objectives: education and socialization of the dangers of Coliform contamination in street food sauces, skills for preventing Coliform contamination in street food sauces and choosing street food sauces according to SNI. Methods: (1) Lecture counseling on the dangers of Coliform contamination in street food sauces, (2) Education on preventing Coliform contamination in street food sauces and examples of choosing street food sauces according to SNI, (3) Discussion. Activity stages: (1) Survey and partner collaboration, (2) Preparation, (3) Socialization and education, (4) Implementation of Appropriate Technology (TTG), and (5) Evaluation. Results: The level of partner knowledge about the dangers of Coliform contamination in street food sauces and how to choose sauces according to SNI standards increased by 78.38% from an average of 4.63 to 8.25. Conclusion: (1) Partners gain knowledge about the dangers of Coliform contamination in snack sauces, (2) Partners gain knowledge and skills in preventing Coliform bacteria contamination in snack sauces and choosing clean and healthy snack sauces according to SNI.